Penerapan Project Based Learning untuk Mengukur Keterampilan Kerja Siswa SMK - Qalbi, Zaenab Zakiyyatun; Rachmawati, Rivanna Citraning; Wardani, Susilo (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2025)
The rapid development of the 21st century demands work skills that must be possessed by superior Indonesian humans, but the facts on the ground show that these work skills are not widely possessed by students. This is reinforced by data from observations made at SMK Negeri 1 Bawen which shows that students who do not understand proper agricultural cultivation techniques even though learning has been carried out at the previous meeting. This condition is also evident from the results of cognitive scores which show 50% of students have not completed or 31 out of 62 students have not met the completeness criteria (KKM) of 75. The purpose of this study was to determine the level of work skills of students of SMK Negeri 1 Bawen through the Project Based Learning model. Descriptive research method with a quantitative approach. The data of this study were obtained from the observation sheet of project-based assessment of work performance by students using work skills indicators. The results showed that the work skills of students in class X ATP (Agribusiness of Plantation Crops) had an average of 74.5 with a good category. In conclusion, the application of Project Based Learning can measure the work skills of students at SMK Negeri 1 Bawen.